Agriculture as a transitional field towards habitus renewal: Examining the impact of technology and social structural change on rural development in Cibodas, West Java - Nirwasita Daniswara; Erwando Erwando (Privietlab, 2025)
This study examines how social change occurs through the transition to smart farming in Cibodas Village, West Java, Indonesia. Using Pierre Bourdieu's concepts of habitus, capital, and field within a constructivist paradigm, this study employed qualitative methods, including participant observation, in-depth interviews, and analysis of policy documents and training materials related to smart farming. The results show that applying IoT technology for automated irrigation for fertilization and microclimate monitoring in smart farming can simplify agricultural operations and transform farmers' habits and village government structures, orienting them toward the use of advanced technology. This shift occurs as cultural capital based on digital technology is transformed into symbolic capital, thereby increasing sales confidence. This shift is particularly pronounced among young farmers, who utilize digital knowledge to simplify agricultural operations and sales mechanisms. However, for elderly farmers, their lack of literacy skills and limited access to information pose a potential disadvantage in facilitating the Cibodas Village. Agriculture in Cibodas serves as a platform for mobilizing and negotiating various forms of capital. This underscores the need for technology adoption to drive change and promote more equitable social development.